KEPEMIMPINAN VISIONER PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) BERDASARKAN KEPMENDAGRI NOMOR 47 TAHUN 1999 - Hanfan, Ahmad; Sumarno, , (PERMANA, 2010)
Perusahaan Daerah Air Minum (PDAM) Is a public company whlch service to fulfill amount of water required. It is in accordance with the mandate of article 37 of Government Regulation number 16 Year 2005 about the development of water supplying system. PDAM actually is not single operator. because the cooperation and private enterprise could also be the operator or organizer. Because or Initial Investment is very big, It Is rarely that cooperation and private enterprise join with the water supplying system business. Due to it is semi-monopoly; the goverment should make the rule/regulatlon which aim to protect consumers /the public as customer. Rule/Regulatlons of the government must restrict the authority of the taps as profit oriented enterprise. To overcome these oustacles, PDAM requires the director or manager who gass the soul of a visionary leadership. Hopefully, with the visionary manager/leader who can face the obstacles that exist so that he can lead the company more advanced againKeyword: Visionary Leadership